Comprehensive Analysis of the Oncogenic, Genomic Alteration, and Immunological Landscape of Cation-Chloride Cotransporters in Pan-Cancer - Wang, Jie; Liu, Wangrui; Xu, Wenhao; Yang, Baofeng; Cui, Mingzhu; Li, Zhen; Zhang, Hailiang; Jin, Chuntao; Xue, Huanzhou; Zhang, Jiaqiang (Frontiers in Oncology, 2022)
Background: Assessing the phenotypic diversity underlying tumor progression requires the identification of variations in the respective molecular interaction in the tumor microenvironment (TME). Despite emerging studies focusing on the association between cation-chloride cotransporters (CCCs) and carcinogenesis, direct evidence that CCCs (KCC2 and NKCC1) mediate tumor progression in pan-cancer remains unclear. Methods: We conducted a comprehensive assessment of the expression, DNA variation profiles, and prognostic, immunologic implications of CCCs based on large-scale pan-cancer population, including 10,967 cancer patients from the Cancer Genome Atlas, 9,162 cancer patients from Genomics Expression Omnibus, 48,834 cancer patients from 188 independent studies and 356 cancer patients from three real-world cohorts. Results: We first found CCCs were highly expressed in most tumors, and prominently associated with prognosis. Kaplan-Meier analysis and Cox regression analysis revealed that KCC2 and NKCC1 significantly predicts survival for patients with cancer, suggesting that CCCs have inconsistent tumorigenesis regulatory mechanisms in cancers. Next, we examined the DNA variation landscape of KCC2 and NKCC1 and their prognostic implications in pan-cancer. The results demonstrated that cancer patients with somatic copy number variation (CNV) of NKCC1 received significantly better outcomes (p<0.05). Besides emphasizing the clinical implications of CNV of CCCs for cancer patients, we found that NKCC1MUT could prominently prolong progression-free survival (p=2.59e-04) and overall survival (p=0.034) compared with NKCC1WT cancer patients possibly via regulation of cell proliferation and oncogenic stress pathways. Additionally, KCC2 positively correlated with the levels of tumor-infiltrating macrophages and CD4+ T cells, but NKCC1 showed significantly widely negative association with tumor infiltrated lymphocytes, suggesting an immune-excluded TME in cancers. Finally, to verify our hypothesis and altered expression of CCCs, IHC analysis was performed to reveal the staining distribution among glioma, clear cell renal cell carcinoma, papillary cell renal cell carcinoma, hepatocellular and breast cancer from multiply real-world cohorts, and validation prominently prognostic implications of CCCs in patients with clear cell renal cell carcinoma.. Conclusion: This study first comprehensively investigated the molecular and clinical role of CCCs, and provided an in-depth understanding of potential oncogenic, immunologic expression and DNA alteration of KCC2/NKCC1 cancers.